Beckman Model CP Constant Flow Paper Electrophoresis Cell, Fraction Collector, and Constat power supply - Hesketh, Dean D.
Electrophoresis uses an electric field to separate particles in a medium (like a gel) based on their size, charge, or a binding affinity.
Keywords: Electrophoresis; Scientific apparatus and instruments; Paper electrophoresis; Electrophoresis--Equipment and supplies; Beckman Instruments, Inc.